Technology adoption and extreme stock risk: Evidence from digital tax reform in China - Kangqi Jiang; Xiaofeng Chen; Jiayun Li; Mengling Zhou (Humanities & Social Sciences Communications)
Abstract The digital reform of tax administration occupies a pivotal role due in enhancing governmental governance capabilities in the digital era. We consider China’s “Golden Tax Phase III” project (GTP3P) as a representative digital reform of tax administration. Utilizing a multi-phase DID model, we analyze the impact of GTP3P on the stock market, with a particular focus on corporate stock price crash risk (SPCR). Our findings reveal a significant reduction in SPCR subsequent to the GTP3P implementation. After performing parallel trend test, dealing with endogeneity concerns, and estimating the double machine learning model, we confirm baseline findings again. Heterogeneity analysis indicates that the influences of GTP3P on SPCR is asymmetrical. In the mechanism analysis, we verified that tax administration reform significantly enhances information disclosure, which guarantees a reduction of SPCR. Finally, we perform a further analysis examining investors’ holding preferences. Contrary to expectations, we observed a decrease in stock liquidity and the shareholding of long-term and fund investors, attributed to the escalated tax burden and diminishing business benefits post-reform. This study presents an innovative perspective on the corporate implications of digitization.